1999
DOI: 10.1023/a:1007514030062
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A total of 202 serum and stool samples from acute hepatitis patients attending the Fever Hospital of Alexandria, Egypt, have been studied to reveal markers of hepatitis virus infection. Anti-HAV IgM were detected in 21 out of 202 sera (10.4%), whereas 201 sera (99.5%) had anti-HAV IgG. The first age attack was in the class-age 0-9 years with 64.7% of anti-HAV IgM positive sera. Among 202 patients, anti-hepatitis E IgG (sample/over cut off > 1.0) was identified in 90 patients (44.5%). The anti-HEV seropositivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Table  5 presents a summary sorted by genotype and also provides characteristics of the sample, genomic regions tested. Genotype 1 seems to be most prevalent as it was found in Central African Republic [34], Sudan [35], Chad [28,35], Egypt [46,62,124], and Namibia [88] followed by genotype 2, which were observed in Central African Republic [34], Chad [35], Namibia [87], and Nigeria [6,89]. Genotype 3 is rare and was found in one Egyptian child [48], one acute hepatitis patient in Mayotte (originally from France) [82].…”
Section: Resultsmentioning
confidence: 99%
“…Table  5 presents a summary sorted by genotype and also provides characteristics of the sample, genomic regions tested. Genotype 1 seems to be most prevalent as it was found in Central African Republic [34], Sudan [35], Chad [28,35], Egypt [46,62,124], and Namibia [88] followed by genotype 2, which were observed in Central African Republic [34], Chad [35], Namibia [87], and Nigeria [6,89]. Genotype 3 is rare and was found in one Egyptian child [48], one acute hepatitis patient in Mayotte (originally from France) [82].…”
Section: Resultsmentioning
confidence: 99%
“…Cross-sectional studies conducted in rural areas revealed very high prevalence of anti-HAV IgG reaching 100% of adults 13. Consumption of common village water, use of indoor dry pits, and contamination of drinking water with sewage represent the major risk factors for HAV acquisition in rural Egypt 16,17. In the past 2 decades, there has been significant emphasis on improving sanitation measures and hygiene in Egypt coupled with extension of municipal potable water, sewage, and solid-waste management systems projects.…”
Section: Hepatitis a Virus (Hav) Infectionmentioning
confidence: 99%
“…Finally, an alternative explanation for the lack of morbidity among anti-HEV incident cases could be that initial asymptomatic infections occur during early childhood with subsequent antibody titer boosting without illness upon re-exposure to the virus [15,16] . However, more virulent genotypes of HEV, mostly genotype 1, could be a cause of sporadic cases of HAV in Egypt [44][45][46][47] . Zoonotic transmission of HEV has been suggested.…”
Section: Genotypic Distribution and Phylogenetic Analysismentioning
confidence: 99%